Tantangan Dan Peluang Penggunaan Fintech Dalam Perbankan Syariah - Mulyana, Iwan; Hamid, Abdul; Syaripudin, Enceng Iip (STAI Al Musaddadiyah Garut, 2023)
The growth of Islamic banks is strongly influenced by the advancement of Fintech. Although Fintech can be a threat, it can also be a partner for Islamic banks. As a result, Fintech in Islamic banking has become important and relevant, especially in the context of economic digitalization and globalization. With Fintech, there are many ways to improve the accessibility, efficiency, and innovation of Islamic financial services. But its implementation presents particular challenges, such as Shariah compliance, cybersecurity, digital literacy, and system integration. This study analyzes the literature on opportunities, problems, and strategies to address the challenges of Fintech adoption in Islamic banking. Through narrative and thematic analysis, the study identifies key opportunities such as improving accessibility, operational efficiency, and product innovation in accordance with Shariah principles. Challenges include Sharia compliance, cybersecurity, customer digital literacy, and system integration. This strategy has been implemented by several Islamic banks in Indonesia, showing that despite obstacles, proper implementation can help overcome these obstacles. This study adds to the number of previous research on Islamic banking and Fintech by providing the most up-to-date analysis of prospects, problems, and strategies to address these issues in the Indonesian context.